EFEKTIVITAS MEDIA PUZZLE PENJUMLAHAN BERBASIS PROBLEM BASED LEARNING (PBL) DALAM MENINGKATKAN KEMAMPUAN OPERASI HITUNG PENJUMLAHAN PADA PESERTA DIDIK KELAS IV - Agus Yuwono; Solehah, Nur Faridatus; Sri Sumartiningsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to evaluate the effectiveness of Addition Puzzle media based on Problem-Based Learning (PBL) in enhancing the addition operation skills of fourth-grade students at SDN Pesantren, Mijen, Semarang. The research employed a Classroom Action Research (CAR) method conducted over two cycles from July to August 2024. Each cycle included planning, action implementation, observation, and reflection. The study's results showed that the application of Addition Puzzle media based on PBL significantly improved students' addition skills and engagement. In the second cycle, the students' learning mastery reached 79.67%, exceeding the Minimum Completeness Criteria (KKM). Thus, PBL-based Addition Puzzle media effectively enhances addition operation skills among fourth-grade students.